Evaluation of the MC-Media Pad® Rapid Aerobic Count Device for the Enumeration of Total Aerobic Counts in a Variety of Foods: Collaborative Study, First Action Official MethodSM 2019.02. (30th March 2020) - Bastin, Benjamin; Klass, Nicole; Crowley, Erin; Agin, James; Lindhardt, Charlotte; Chollet, Renaud
Abstract: Background: The MC-Media Pad ® Rapid Aerobic Count (RAC) is a ready-to-use culture device combining a test pad coated with medium and water absorption polymers that are designed for the rapid quantification of total aerobic bacteria in food products. Objective: The MC-Media Pad RAC was compared to the U.S. Department of Agriculture Food Safety and Inspection Service Microbiology Laboratory Guidebook, Chapter 3.02: Quantitative Analysis of Bacteria in Foods as Sanitary Indicators for raw ground pork and the Standard Methods for the Examination of Dairy Products, Chapter 6: Microbial Count Methods for yogurt drink. Method: The candidate method was evaluated against the reference methods using a paired study design in a multi-collaborator study, following the current AOAC INTERNATIONAL Official Methods of Analysis SM Appendix J guidelines. Three target contamination levels (low, medium, and high) were evaluated. MC-Media Pad RAC devices were enumerated after 24 and 48 h of incubation. Results: Plate counts obtained by both methods were log10 -transformed and the difference of means (including 95% confidence intervals), repeatability SD, and reproducibility SD were determined for each contamination level. All 95% confidence intervals for mean difference fell easily within ±0.10, the performance requirement being ±0.5. Conclusion: The MC-Media Pad RAC (for both 24 and 48 h) and both reference methods for each contamination level were therefore shown to be equivalent, with 97.5% confidence. Highlights: The new method offers a convenient alternative to the reference methods for detection of aerobic plate count in food products, yielding reliable and comparable results in 24 or 48 h compared to 48 h for the reference methods.